Establishing Technology Park to Support the Commercialization of Intellectual Property in Higher Education Institutions - Hoang Long, Luu (VNU Journal of Science: Policy and Management Studies, 2025)
On December 22 nd , 2024, the Politburo issued Resolution No. 57-NQ/TW on making breakthroughs in the development of science, technology, innovation, and national digital transformation. Among its proposed solutions is the development of higher education institutions into strong research entities that closely integrate research, application, and training. Surveys indicate that in recent years, higher education institutions have achieved certain results in both basic and applied research. However, the commercialization of intellectual property — an outcome of applied research — still faces invisible barriers, particularly in policies related to intellectual property management. Based on a survey conducted at Vietnam National University, Hanoi, along with 20 higher education institutions in northern provinces, 5 in central provinces, and 19 in southern provinces, the study identifies key challenges in the commercialization of intellectual property at these institutions and explores the root causes of such challenges. Drawing on the survey results, this article proposes the establishment of “Technology Parks” to support the commercialization of intellectual property in higher education institutions. These parks aim to encourage innovation, manage the exploitation and protection of intellectual property, and contribute to building a knowledge-based economy that supports national socio-economic development.